Many Third Ways: Alternative Conceptions of Democracy in Russia during the Perestroika - Asenbaum, Hans (Momentum Quarterly, 2012)
The six years of Soviet perestroika represent a time of radical change, consciously experienced and actively promoted by society and the political elite. In this special period the loosening of social and media censorship enabled the emergence of informal organisations, promoting their various ideas of system alternatives in a loud democracy movement. The criticism of repressive state socialism and unjust capitalism opened a perspective on many Third Ways, which were vividly discussed in a time of rapid public politicisation. The mass demonstrations and promoted alternatives of the Russian informal movement are, however, ignored by historic and social sciences and are thus almost forgotten. This paper tries to counteract this oblivion and to incorporate those ideas into current discussions about a re-democratisation of democracy or socialist alternatives respectively. Thus a new perspective on the relationship of democracy and socialism is taken into account. After a historic overview of the Russian informal movement, the various reform suggestions and system alternatives are illustrated. Since almost no literature on this topic exists, sixteen qualitative interviews with activists of various ideological backgrounds were taken in Moscow. Finally, the illustrated ideas will be put into the context of current alternative discussions of democracy.
Keywords: Alternative models of democracy; history of socialist ideas; Russia; perestroika; system transformation; civil society; democracy movement